Air assistance and spray volumes on the coverage, droplet density, and spray deposition in melon plants - Oliveira Fontes, Larissa; Lopes de Freitas, Francisco Cláudio; Martins Teixeira, Mauri; Nunes Silva, Ítalo; Robson (Comunicata Scientiae, 2024)
This study aimed to evaluate the influence of air assistance on the coverage, droplet density, and deposition of the mixture volume applied to melon plants. The experiment was conducted in a completely randomized design set up in a 4 x 4 x 2 factorial arrangement referring to four spray nozzles (AVI 110-02, TT 110-02, AVI 110-03, and TT 110-03), four mixture volumes (140, 200, 300, and 400 L ha-1), and two application techniques (with and without air assistance), at a constant working pressure of 300 kPa. Deposition analysis was performed by using a bright blue dye, and the coverage pattern and droplet density were analyzed using water-sensitive paper tags attached to the adaxial and abaxial surfaces of the leaf blade of melon plants. Air assistance in the spray boom improved the deposition of the mixture sprayed on melon leaves only when using nozzle TT 110-02, whereas nozzles TT 110-03, AVI 110-02, and AVI 110-03 were not influenced by air assistance. Coverage and spray deposition on the adaxial leaf surface increased with the mixture volume applied for all nozzles. The technique using water-sensitive tags is not efficient to evaluate droplet density when working with high spray volumes.